SUPRAVENTRICULAR ARRHYTHMIAS AND HIGH-DEFINITION ECG IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE, RECEIVING BRONCHOLYTIC THERAPY - Kh. Kh. Shugushev; M. V. Gurizheva; V. M. Vasilenko (Российский кардиологический журнал)
The study aimed at the assessment of broncholytic therapy effects on supraventricular arrhythmia structure and highdefinition ECG characteristics of atrial complex among patients with chronic obstructive pulmonary disease (COPD). In total, 144 COPD patients and 35 controls underwent 24-hour ECG monitoring and high-definition ECG with time and spectral mapping of atrial complex. Theophylline and seretide therapy resulted in reduced supraventricular arrhythmia incidence among patients with mild to moderate COPD. Among participants with severe COPD, theophylline therapy was associated with increased mean number of supraventricular extrasystoles. Seretide therapy in both groups and theophylline therapy in patients with moderate COPD demonstrated beneficial effects on high-definition ECG parameters of atrial complex, as well as spectral and time mapping characteristics. Therefore, seretide could be a better broncholytic choice in patients with severe COPD and supraventricular arrhythmias.